Development of a low-cost, simple-to-use microfluidic device for analysis of glioblastoma multiforme movement - Kreznor, Abigail Fay (My University, 2024)
Glioblastoma multiforme (GBM), a type of adult primary brain cancer, exhibits rapid tumor progression and extremely low survival rates. The cancerous cells utilize the signaling pathways within the central nervous system to encourage cancer-promoting behaviors that manipulate the immune response and degrade the extracellular matrix to aid tumor proliferation. Additionally, GBM applies cellular mechanisms to enable mobility through both perivascular spaces and constrictive tissues within the brain. These characteristics of GBM greatly diminish the effectiveness of traditional cancer treatment methods. The higher age of patients diagnosed with GBM contributes to other significant issues during treatment, such as comorbidities and higher risk of surgical complications. A better understanding of GBM, especially how the tumor microenvironment influences the mobility of this cancer, could be vital to developing improved therapeutics. While many established methods have been used to study the cell environment and resulting migration, the majority of these techniques suffer from instability, imprecision, and providing only endpoint analysis. Microfluidic devices offer an alternative platform for cell studies with significant advancements by coupling enhanced fluidic control with real-time, live cell imaging. Gradient-producing devices can create complex and stable experimental conditions for more elaborate modeling of the tumor microenvironment. Although traditional microfluidics fabrication requires expensive equipment and advanced training, substantial progress in the field of 3D printing has greatly increased the capabilities of this fabrication technique while simultaneously reducing the startup costs and level of expertise needed. This work presents the development of a low-cost and simple-to-use microfluidic device to study GBM movement. The initial exploration of LCD-based and digital light projection resin 3D printing included the optimization of printing and post-print processing for the fabrication of microfluidic devices. Critical material properties of the cured resin, such as temperature resistance, autofluorescence, and biocompatibility, were assessed. Out of the multiple sealing methods examined, 3M™ microfluidic tape was selected as the best reversible option, and a treatment procedure was developed to enable cell culture on its adhesive surface. A protocol for casting polydimethylsiloxane devices from resin 3D-printed molds was created, and an appropriate environment for cell culture was maintained using a microscope stage incubator and a miniature heating pad for external tubing. After testing a variety of methods for fluidic operation, a miniaturized and automated system was implemented. Confirmation of gradient formation, the key factors that influence the gradient profile and stability, and a basic analysis of shear stress within the device were completed. Finally, initial results from GBM migration studies were reported to provide proof-of-concept for the devices developed in this work.
Keywords: Glioblastoma multiforme; Microfluidics; Cell migration; Resin 3D printing